Insights into Early Language Development: An Investigation of Speech Acquisition in 25-Month-Old Toddler - Aprilia, Fitria; Neisya, Neisya (JOLLT Journal of Languages and Language Teaching, 2024)
This study delves into the early language development of a 25-month-old toddler, emphasizing phonological aspects encompassing consonants, vowels, and diphthongs. Conducted in Palembang in December 2023, the research employs a qualitative methodology utilizing a case study approach. The investigation aims to address the crucial role of phonological development in early language acquisition and its implications for linguistic theory and pedagogy. By focusing on the phonological repertoire of a toddler identified as "M. AH," this study contributes to bridging the gap in research regarding early phonological development in Bahasa Indonesia-speaking children. Key research questions include identifying the range of phonological elements mastered by the toddler and exploring potential factors influencing their linguistic development. The analysis reveals the toddler’s adeptness in articulating various phonemes, including 14 consonants, six vowels, and several diphthongs, within their linguistic environment. These findings shed light on the intricate process of early language acquisition and underscore the importance of understanding phonological development in diverse linguistic contexts. Methodologically, the research utilizes direct observation and recording techniques to capture and analyze the toddler’s linguistic interactions and productions. Overall, this study provides valuable insights into the early stages of language acquisition, offering implications for both research and practice in child language development and education.